D-Fusion SLAM: A VSLAM system optimized by integrating depth information and RGBD feature points - Zheng, Qingchun; Wu, Moudong; Zhu, Peihao; Yang, Bin; Li, Shubo (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
This paper introduces D-Fusion SLAM, an advanced VSLAM system based on ORB-SLAM2. D-Fusion SLAM integrates depth information to enhance feature selection, aiming to improve accuracy and speed in visual SLAM applications. The system mainly comprises two modules: an image grid filtering module based on grayscale information and a feature selection module integrating depth information. These modules effectively eliminate redundant and useless features, ensuring highquality features for pose estimation. We tested D-Fusion SLAM on the TUM dataset and compared it with ORB-SLAM2. Experimental results demonstrate that D-Fusion SLAM outperforms ORB-SLAM2, significantly enhancing the system's accuracy and robustness.